2008
DOI: 10.1002/marc.200700779
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Uptake of DNA Block Copolymer Micelles with Different Shapes

Abstract: The cellular uptake of DNA block copolymer micelles composed of DNA‐b‐PPO in Caco‐2 cells was studied. In particular it was investigated if the shape of micelle aggregates influences the internalization. Rod‐like polymeric particles were taken up 12 times more efficiently than their spherical counter parts although they were composed of the same constituents. Furthermore, it was observed that internalization of all the micelle systems was more efficient than the pristine DNA controls. A cytotoxicity assay prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 19 publications
3
91
0
3
Order By: Relevance
“…The positive charge of rod GNP probably enhances its interaction with cell membranes and results in increased cellular uptake. The potential infl uence of rod-shape on increased cellular uptake may not be ruled out since similar observations were made in the literature where rodlike polymeric micelles were taken up to a higher extent than their spherical counter parts (Alemdaroglu et al, 2008).…”
Section: Resultsmentioning
confidence: 88%
“…The positive charge of rod GNP probably enhances its interaction with cell membranes and results in increased cellular uptake. The potential infl uence of rod-shape on increased cellular uptake may not be ruled out since similar observations were made in the literature where rodlike polymeric micelles were taken up to a higher extent than their spherical counter parts (Alemdaroglu et al, 2008).…”
Section: Resultsmentioning
confidence: 88%
“…24 In particular, an AON micelle has shown great potential in cancer therapy. [48][49][50] PPO-b-DNA micelles were equipped both with a hydrophobic anticancer drug and a targeting unit. Therby, doxorubicin accumulated in the core of the AON aggregates by simple mixing while the folic acid targeting units were incorporated into the carrier system by hybridization (Fig.…”
Section: Applications Of Aons and Their Nanocomposites Utilization Ofmentioning
confidence: 99%
“…Uptake studies into the cancerous Caco 2 cell line revealed an internalization behavior that is strongly dependent on the geometry of the nanostructures [157]. It turned out that the rod-like aggregates were taken up to a much greater extent than ss and ds spherical micelles.…”
Section: Amphiphilic Dna Block Copolymersmentioning
confidence: 99%